Perilaku Pencegahan COVID-19 pada Ibu Hamil - Putu Monna Frisca Widiastini; Kadek Diah Ayu Pratidina; Desak Ketut Sugiartini (Journal of Telenursing (JOTING), 2022)
This study aims to determine the preventive behavior of COVID-19 in pregnant women in the Gerokgak I Health Center Work Area. The type of research used is descriptive quantitative with a cross-sectional approach. The results showed that most pregnant women had good knowledge about COVID-19 (97.6%), while the COVID-19 prevention behavior in pregnant women was classified as poor with a percentage of 65.9%. In conclusion, most pregnant women have good knowledge about COVID-19, but preventive behavior is not good. Keywords: Pregnant Women, Knowledge, COVID-19 Prevention Behavior